Follicular dendritic cells, conduits, lymphatic vessels, and high endothelial venules in tertiary lymphoid organs: Parallels with lymph node stroma - Stranford, Sharon; Ruddle, Nancy H. (Frontiers in Immunology, 2012)
In this communication, the contribution of stromal, or non-hematopoietic, cells to the structure and function of lymph nodes (LNs), as canonical secondary lymphoid organs (SLOs), is compared to that of tertiary lymphoid tissue or organs (TLOs), also known as ectopic lymphoid tissues. TLOs can arise in non-lymphoid organs during chronic inflammation, as a result of autoimmune responses, graft rejection, atherosclerosis, microbial infection, and cancer. The stromal components found in SLOs including follicular dendritic cells, fibroblast reticular cells, lymphatic vessels, and high endothelial venules and possibly conduits are present in TLOs; their molecular regulation mimics that of LNs. Advances in visualization techniques and the development of transgenic mice that permit in vivo real time imaging of these structures will facilitate elucidation of their precise functions in the context of chronic inflammation. A clearer understanding of the inflammatory signals that drive non lymphoid stromal cells to reorganize into TLOs could allow the design of therapeutic interventions to impede the progression of autoimmune activity, or alternatively, to enhance anti-tumor responses.